Kategoria Innego jako element dyskursu tożsamościowego w średniopolskich katalogach władców – perspektywa krzyża - Hawrysz, Magdalena (Poznańskie Studia Polonistyczne. Seria Językoznawcza, 2016)
This sketch concerns the notions of groups that were considered aliens by the old Poles. Methodologically the work remains in the circle of ethnolinguistic research. The analysis uses the tools developed by the theory of linguistic image of the world. Material has been excerpted from 4 catalogs of rulers created in the period from the seventeenth to the eighteenth century. In the observed catalogs, there are three points of view, from the perspective of which the alien is categorized; these are the optics of a sword, cross, crown. The reconstruction of the infidels’ image in the article is carried out in the context of the functions this category plays in the era of shaping and preservation of national identity in a multi-ethnic and multi-religious country.